TRANSLATION ERRORS OF ENGLISH-INDONESIAN TEXT IN BASIC TRANSLATION CLASS - Mustathira; Fatimah Hidayahni Amin (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
This study aims at finding out (1) the kinds of translation errors made by the students, (2) the dominant translation errors made by the students (3) the students’ difficulties in translating English to Indonesian texts in UIM Al Ghazaly Makassar. This research used a descriptive qualitative method which intended to collect and analyze data by using the concept from Miles, Huberman, and Saldana (2014). The subject of this research was the third semesters of English Education Department in UIM Al Ghazaly Makassar. There were10 students who were chosen purposively as the participants of the research. The object of this research was errors in translating English to Indonesian Text. The instrument of this research is the text of paragraph. The test was used to get data about the students’ error in English to Indonesian translation text. The results of this research showed that the students made errors in English to Indonesian translation text, it found the kinds, the dominant, and the difficulties error made by students in translating a text. The kinds of error were (1) inversion of meaning students made about 2 errors, (2) omission of meaning made about 3 errors, (3) addition of meaning, made about 2 errors, and (4) Deviation of meaning, made about 3 errors. The dominant errors were, (1) Morphological aspect, made about 3 errors, (2) Lexical aspect, students made error with 3 errors, and (3) Syntactic aspect, the error made by students about 3 errors. The difficulties that student found in translate the text is lexical meaning, grammatical meaning, contextual meaning, textual meaning, and socio-cultural meaning, it can be conclude that the difficulties faced by students in translating a discourse, both in terms of lexical meaning, grammatical meaning, contextual meaning, textual meaning, and socio-cultural meaning, it can be said that the errors produced by all students occur repeatedly, although some translate it using the internet, the rest use the manual method